2000
DOI: 10.1063/1.1320866
|View full text |Cite
|
Sign up to set email alerts
|

Direct characterization of terahertz radiation from the dynamics of the semiconductor surface field

Abstract: We report on a time-resolved electro-optic sampling of the photocarrier-induced surface field dynamics by a midband gap probe beam from a femtosecond fiber laser. By measuring the ultrafast surface field variation, we are able to derive the undistorted terahertz wave form radiated from the semiconductor surface that is excited by the femtosecond laser pulses. The derived wave form agrees well with the directly measured terahertz radiation at the far field. The peak frequency of terahertz radiation is found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The radiated THz field is proportional to the optical pump power and is due to a combination of OR, 176,242 bulk DFG 243 and photocarrier acceleration in the surface field of the semiconductor. 244,245 T-ray emission from semiconductor surfaces is influenced by the magnetic field surrounding the emitter, 246,247 which can be used to switch or enhance the generation efficiency. 248~252 T-ray emission from an unbiased GaAs wafer in a switchable magnetic field is shown in Fig.…”
Section: Pulsed Photomixingmentioning
confidence: 99%
See 1 more Smart Citation
“…The radiated THz field is proportional to the optical pump power and is due to a combination of OR, 176,242 bulk DFG 243 and photocarrier acceleration in the surface field of the semiconductor. 244,245 T-ray emission from semiconductor surfaces is influenced by the magnetic field surrounding the emitter, 246,247 which can be used to switch or enhance the generation efficiency. 248~252 T-ray emission from an unbiased GaAs wafer in a switchable magnetic field is shown in Fig.…”
Section: Pulsed Photomixingmentioning
confidence: 99%
“…397,398 Two-color EOS, with time-delayed collinear pulses transmitted through a GaAs sample, has been used to study T-ray generation from surface field dynamics. 245 Using ultrafast optical excitation pulses, T-rays have been used to observe photocarrier generation and the subsequent screening processes in semiconductors. 282,399,400 Optical-pump and THz-probe experiments have also enabled a form of near-field imaging with a dynamic aperture, as detailed in Sec.…”
Section: Solidsmentioning
confidence: 99%
“…Other workers have shown that the surface depletion field present at the semiconductor/air interface can accelerate photogenerated carriers in the same manner as the THz planar emitters described above. 39,[47][48][49][50][51][52][53] Because this type of transmitter does not have a metal electrode deposited onto it, a THz pulse is generated in both the forward and reflected directions. This process has also been investigated with Monte Carlo simulations.…”
Section: Planar Antennasmentioning
confidence: 99%
“…In fact, the polarity of the pulse reverses below 120 K. 152,153 It is also possible to monitor the surface field directly using transmission electrooptic sampling, and compare the results with the emitted waveform. 51 A biased metal film on the surface can control the surface depletion field, which allows the dependence of the carrier dynamics on the surface field to be explicitly measured. 45 The temperature dependence of the carrier scattering times in GaAs at temperatures up to 900 K has been measured.…”
Section: Bulk Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation